Students Readiness Of SDN Jatibarang to Facing Hydrometeorological Disaster - Aris Munandar; Sucahyanto; Oot Hotimah; Cahyadi Setiawan (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract Indramayu has the potential for environmental disasters, including hydrometerological disasters. The need for knowledge about disasters that threaten the environment. It is important to introduce school-aged children to the dangers that threaten the environment because it can disseminate information to the home environment and community environment. Community service activities were carried out offline/face to face on July 26 2024. The subjects and targets were students of SDN 1 Jatibarang, especially class 6, totaling 31 students. The method used is outreach using interesting videos about hydrometerological disasters. Evaluation is used by comparing presets and posts. The results of the socialization of class 5 participants enthusiastically participated in the activity. Socialization uses lecture methods, video presentations and questions and answers. The results of the pretest and posttest comparison showed that there was a significant difference in the length of time for providing family supplies before socialization, the average value was 46, after socialization the average value was 90, there was a striking difference, namely 44. These results indicate that participants did not understand how long supplies would take. the family's equipment will survive. The very small difference is about the factors that cause drought. Before socialization the value was 51, after socialization the value was 60, there was a difference of 9. Keywords: Preparedness, Disaster, Hydrometerology Abstrak Indramayu memiliki potensi bencana lingkungan diantaranya hidrometerologis. Perlu adanya pengetahuan tentang bencana yang mengancam dilingkungannya. Pengenalan bahaya yang mengancam lingkungan pada anak usia sekolah menjadi penting karena dapat menyebarkan informasi kepada lingkungan rumah dan lingkungan masyarakat. Kegiatan pengabdian pada masyarakat dilakukan secara luring/ tatap muka pada tanggal 26 Juli 2024. Subyek dan sasaran adalah Siswa SDN 1 Jatibarang terutama kelas 5. dengan jumlah 31 siswa. Metode yang dilakukan dengan sosialisasi dengan menggunakan video yang menarik tentang bencana hidrometerologis. Evaluasi digunakan dengan membanding pretets dan posts Hasil sosialisasi peserta kelas 6 antusias mengikuti kegiatan. Sosialisasi dengan metode ceramah, penayangan video dan tanya jawab. Hasil perbandingan pretest dan posttest menunjukan perbedaan yang signifikan tentang lama persediaan family kit sebelum sosialisasi rata-rata nilai 46, setelah sosialisasi nilai rata-rata 90 ada selisih yang mencolok yaitu 44 . Hasil ini menunjukan peserta belum paham tentang persediaan famili kit untuk berapa lama waktunya. Perbedaan yang sangat kecil yaitu pertanyaan faktor-faktor yang menyebabkan kekeringan. Sebelum sosialisasi nilainya 51 setelah sosialisasi nilainya 60 ada selisih 9. Kata kunci : Kesiapsiagaan, Bencana, Hidrometerologis